S.JUMAǴULOVTÍŃ YUMORLÍQ GÚRRIŃLERINDE OBRAZ JARATÍW ShEBERLIGI - Kudiyarova, Rıslıxan Kadirbaevna (SCIENCE and SOCIETY, 2026)
The article specifically addresses the issue of the humorous image in S. Zhumagulov's works. Through the image, the character's inner world is revealed. If the humor is through images, it seems as if the writer is raising a problem. Let us discuss and discuss how the writer S.Zhumagulov depicted the problem of the humor image in his short-story works.